Organizational and production components at the stage of engineering preparation of an investment and construction project, their role in managing the cycle of construction production - Shebek, N.; Dubynka, O.; Tugai, A.; Yavtushenko, D. (Ways to Improve Construction Efficiency, 2019)
One of the forms of organizational design is the system of construction production in the context of investment and construction real estate projects. The distribution of the construction industry into an organizational and production structure makes it possible to determine the main goals and functions of the participants in the construction process using the model example. Investment and construction real estate projects are directly related to the technological process of construction production. Efficiency and rhythm of construction projects is achieved through a timely and coordinated approach of setting tasks and making fundamental decisions at each organizational and managerial level, first of all this is reflected at the stage of engineering preparation of a construction project. The optimal definition of priorities at the stage of engineering preparation of the construction site, the minimum use of resources and the opening of work for the next stages of construction production ensures the production process with the principles of proportionality, directness and continuity - for more efficient production management, organizing the interaction of participants in construction and investment projects and future development of housing construction in Ukraine. It is proposed to scientifically investigate and put into practice the system model of interaction between organizational components and production environmental factors for the effectiveness of the entire system and its individual elements.